THE FEATURES OF ECOLABELING OF FOOD STUFF IN UKRAINE - Архіпова, Г.; Проценко, Д.; Тройченко, О. (Proceedings of National Aviation University, 2012)
The article is dedicated to the problem of quality and safety of food stuff in Ukraine. It deals withcontamination of food products by chemical substances and forming of gene modified organisms whichimpact the quality of the products. Additionally, some food products have been tested and ecolabeling usedin Kyiv supermarkets has been checked and studied